PEMBERDAYAAN PENGRAJIN KERIS (EMPU) MELALUI PENGUATAN MODAL INTELEKTUAL DAN PEMASARAN DIGITAL DI DESA AENG TONG TONG KABUPATEN SUMENEP - Mohammad Herli; Nur Qoudri Wijaya; Mar'a Elthaf Ilahiyah (Jurnal Abdi Insani, 2023)
This service activity aims to empower keris craftsmen (empu) in Aeng Tong Tong Village, Sumenep Regency, through strengthening intellectual capital and digital marketing. The background of this activity includes the challenges artisans face in the era of digitalization and market changes. Challenges have the weak capacity of craftsmen to manage human capital, structural capital, and relational capital. These three components are essential for keris artisans to achieve sustainable performance. This activity aims to empower keris craftsmen (empu) in Aeng Tong Tong Village by strengthening intellectual capital in managing their business. In addition, management, finance, and marketing aspects are also a concern in this community service activity. The activity implementation involves training and intensive assistance to artisans. The process includes the registration of business licenses to strengthen structural capital, followed by training and financial management assistance to enhance human capital. Then, empowerment through digital marketing training to strengthen relational capital. Community service activities include increasing the ability of artisans to understand and implement intellectual capital. First, there has been an improvement in human capital, including an understanding of business and financial management. Second, there is a strengthening of structural capital in the form of availability of business legality; and thirdly, increasing market access through digital marketing as a means of marketing products, which in this case also means strengthening relational capital. This activity contributes to maintaining local cultural heritage while adapting to changing times. This service activity contributes to improving the management of keris artisans in Aeng Tong Tong Village. This collaborative effort stimulates local economic growth and strengthens the artisan community, in line with the spirit of sustainable development.